TRI HITA KARANA IN THE NYASTRA TRADITION: WELCOMING SARASWATI HOLY DAY - Ida Bagus Made Wisnu Parta; Desak Putu Eka Pratiwi; Made Rusmiati (International Conference on Multidisciplinary Research Perspective, 2025)
Bali has many diverse traditions, including traditional ceremonies, festivals, religious rituals, arts, and many more. The traditions in Bali are inseparable from the teachings of Tri Hita Karana. So that the tradition continues to exist and thrives creating harmonious vibrations in Balinese society. One of the traditions in Bali to commemorate the holy day of Saraswati, namely Nyastra means pursuing literature which tends to have an implicit meaning of "believing in literature". A person who performs nyastra performs brata (fasting) activities. The purpose of this study is to describe the implementation of the teachings of Tri Hita Karana on the holy day of Saraswati in preserving the tradition of Nyastra. The research method used is a literature study and semiotic theory. The results of this study are to interpret the teachings of Tri Hita Karana on the holy day of Saraswati in preserving the tradition of Nyastra. The implementation of the forms of Nyastra tradition to prepare for the holy day of Saraswati, namely cleaning lontar, reading and interpreting lontar texts, and writing lontar. The relationship between the Nyastra tradition as a form of symbiosis with the celebration of Saraswati Day can be interrelated to create harmony in worshiping knowledge.